2004
DOI: 10.1111/j.0953-816x.2004.03296.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral inhibition and habituation of the human auditory cortex

Abstract: The goal of this study was to compare the lateral inhibition and the habituation in the human auditory cortex, two important physiological effects during auditory processing that can be reliably measured by means of magnetoencephalography when recording auditory evoked fields. Applying 40-Hz amplitude-modulated stimuli allowed us to record simultaneously the slow transient evoked and the steady-state fields and thus to characterize the lateral inhibition and the habituation effect in primary and non-primary au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 21 publications
7
76
0
1
Order By: Relevance
“…Our target notched music introduced a functional deafferentation of auditory neurons corresponding to the eliminated frequency band, and because this frequency band overlapped the individual tinnitus frequency, the notched music no longer stimulated the cortical area corresponding to the tinnitus frequency, although it still excited surrounding neurons. Thus, the neurons, which were not stimulated due to the notch, were presumably actively suppressed via lateral inhibitory inputs originating from surrounding neurons (14,31,32). Alternatively, listening to the target notched music could have induced synaptic and/or cellular plasticity mechanisms (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our target notched music introduced a functional deafferentation of auditory neurons corresponding to the eliminated frequency band, and because this frequency band overlapped the individual tinnitus frequency, the notched music no longer stimulated the cortical area corresponding to the tinnitus frequency, although it still excited surrounding neurons. Thus, the neurons, which were not stimulated due to the notch, were presumably actively suppressed via lateral inhibitory inputs originating from surrounding neurons (14,31,32). Alternatively, listening to the target notched music could have induced synaptic and/or cellular plasticity mechanisms (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…For ASSR analysis, the grand-averaged magnetic field signals within the time range from 0.5 to 1 s were used for single equivalent current dipole estimations (43), and the maximal source strength for each condition and hemisphere was calculated by using the source space projection technique (44). For the N1m analysis, the grand-averaged magnetic fields were 30 Hz low-pass filtered and baseline corrected (31,32,45). Thereafter, the maximal source strength for each condition was calculated in a manner similar to the ASSR source strength calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the classical lateral inhibition concept (von Békésy, 1967; Suga, 1995; Pantev et al, 2004;Okamoto et al, 2005Okamoto et al, , 2007 can account for sharpening of frequency tuning in the central auditory system. Afferent neural inputs consist not only of excitatory, but also of broadly tuned inhibitory inputs, which suppress surrounding neural activities resulting in improved spectral contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Given that tonotopic representations are retained up to the level of the primary auditory cortex (Kaas & Hackett, 2000), it is likely that segregation of tone sequences in the cochlea is transferred up the ascending auditory system. Additional inhibitory processes between neurons responsive to different frequencies in the auditory cortex have been proposed to enhance frequency-based segregation (Bee & Klump, 2004;Fishman et al, 2004;Kanwal et al, 2003;McCabe & Denham, 1997), and recent evidence shows that inhibition operates on the N1 (Pantev et al, 2004;Sable, Low, Maclin, Fabiani, & Gratton, 2004). Inhibition between neurons that are tuned to different frequencies in the auditory cortex might enhance frequency-based segregation by sharpening the tuning curves in individual neurons, thus leading to less overlap in the populations of neurons that are responding to the alternating A and B tones.…”
Section: Evidence For Distinct Mechanisms Of Stream Segregationmentioning
confidence: 99%